BETWEEN SINES AND COSINES: AN X-RAY OF UNIVERSITY ADMISSIONS - Márquez, Dalia Imelda Castillo; López, Georgina Elizabeth Partida; Flores, Alan Roberto Figueroa (Seven Editora, 2025)
The purpose of this study is to describe the prior knowledge of trigonometry among students entering higher education in basic sciences and engineering. A diagnostic test was administered to 21 students at the Autonomous University of Nayarit, using a 10-item instrument that assessed fundamental concepts: radians, conversion of angular units, trigonometric ratios, trigonometric functions, the Pythagorean theorem, and trigonometric identities. The results reveal significant deficiencies in the mastery of trigonometric content essential for academic performance in exact sciences and engineering careers. The average percentage of correct answers was 48.6%, with particular weakness in converting degrees to radians (38.1% correct), applied trigonometric ratios (38.1%), trigonometric functions (38.1%), and the Pythagorean theorem (38.1%). These findings highlight the need to implement academic leveling strategies that strengthen basic mathematical skills prior to the start of higher-level courses, thus ensuring better academic trajectories and reducing failure and dropout rates.DOI: https://doi.org/10.56238/sevened2025.029-116